Meningkatkan Motivasi Belajar Pakat Melalui Model PBL pada Peserta Didik SD Santa Ursula BSD - Yustina Dina Yunianti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to determine the improvement of learning motivation and affective outcomes in the dimensions of teamwork and critical thinking through the Problem-Based Learning (PBL) model among students at Santa Ursula BSD Elementary School. The research is based on the issues of low learning motivation, lack of student engagement in learning, and the need to enhance social skills within the context of Catholic Religious Education and Character Education. This study employs classroom action research, with steps including planning, implementation, observation, and reflection in each cycle. The research consists of two cycles conducted with third-grade students in Phase B at Santa Ursula BSD Elementary School, focusing on the subject